Distribución funcional del ingreso en el sector industrial argentino, 1935-2019: Valor agregado, remuneración al trabajo, ocupación y salarios - Juan M. Gra\~na; Lucas Terranova (Universidad de Buenos Aires, Centro de Estudios sobre Población, Empleo y Desarrollo (CEPED), 2020)
– The main objective of this Working Paper is to present a long-term series (1950-2019) for the functional distribution of income in the Argentinean manufacturing sector. For this purpose, the work is divided according to the methodologies used: linear interpolation for the base years 1986, 1993 and 2004; rate of variation for 1950 - 1986. At the same time, recovering methodologies used by CEPED, we present series of wage share by quality of the labor linkage, labor cost and real wage for the years in which the necessary information was available. Additionally, a long-term series (1935-2019) is presented for the product, both at current and constant prices, for manufacturing productivity and for manufacturing jobs.
Keywords: C82; E01; J31; L60; 330; Compensation of employees; manufacturing sector; aggregate sector; values